2007
DOI: 10.1111/j.1471-0528.2007.01384.x
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent oxytocin with dinoprostone pessary versus dinoprostone pessary in labour induction of nulliparas with an unfavourable cervix: a randomised placebo‐controlled trial

Abstract: Objective To compare concurrent oxytocin with dinoprostone pessary versus dinoprostone pessary in labour induction for nulliparas with an unfavourable cervix.Design A randomised double-blind study.Setting University Malaya Medical Centre, Malaysia.Population Nulliparas at term with intact membranes, Bishop score £ 6 and admitted for labour induction.Methods All women received 3 mg dinoprostone pessary for labour induction. Those randomised to the oxytocin arm received oxytocin infusion started at 1 mu/minute a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 21 publications
4
18
2
Order By: Relevance
“…In the second study, Tan et al [9] compared dinoprostone pessary + oxytocin and placebo + oxytocin in 114 patients with an unfavorable cervix and reported that concurrent vaginal dinoprostone + intravenous oxytocin for labor induction in term women with premature rupture of membrane did not expedite delivery or improve patient satisfaction. In another study conducted by the same authors [15], 220 patients were randomized to receive either pessary + oxytocin or pessary only, and the investigators found concurrent oxytocin infusion with dinoprostone pessary did not significantly increase the vaginal delivery rate within 24 h but reduced the requirement for repeat dinoprostone and improved maternal satisfaction with the birth process. In our trial, only 19.4% of the patients in the dinoprostone group required oxytocin infusion due to unsatisfactory uterine contractions.…”
Section: Discussionmentioning
confidence: 99%
“…In the second study, Tan et al [9] compared dinoprostone pessary + oxytocin and placebo + oxytocin in 114 patients with an unfavorable cervix and reported that concurrent vaginal dinoprostone + intravenous oxytocin for labor induction in term women with premature rupture of membrane did not expedite delivery or improve patient satisfaction. In another study conducted by the same authors [15], 220 patients were randomized to receive either pessary + oxytocin or pessary only, and the investigators found concurrent oxytocin infusion with dinoprostone pessary did not significantly increase the vaginal delivery rate within 24 h but reduced the requirement for repeat dinoprostone and improved maternal satisfaction with the birth process. In our trial, only 19.4% of the patients in the dinoprostone group required oxytocin infusion due to unsatisfactory uterine contractions.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In this study the use of dinoprostone gel for induction of labour, improved the Bishop score so chances of successful induction also increased.…”
Section: Discussionmentioning
confidence: 68%
“…Because to our knowledge there was no study on sustained-release dinoprostone vaginal pessary with concurrent high-dose oxytocin infusion compared with sustained-release dinoprostone vaginal pessary followed 6 h later by high-dose oxytocin infusion for labor induction available at trial inception, power calculation was based on a study of labor induction in women with prostaglandin concurrent oxytocin compared with prostaglandin, which showed a 48.6 versus 35.9% vaginal delivery rate within 24 h [8]. Setting significance at 5%, power at 80%, and a one-to-one recruitment ratio, 234 women were required in each arm.…”
Section: Methodsmentioning
confidence: 99%
“…There are 5 studies on concurrent oxytocin infusion with prostaglandin administration for cervical ripening and labor induction [4,5,6,7,8]. Three of these studies have shown a shorter induction-to-delivery interval with concurrent oxytocin infusion with a prostaglandin agent at the initiation of labor, but the other 2 studies did not demonstrate a significantly shorter induction-to-delivery interval with concurrent oxytocin infusion [4,5,6,7,8]. However, in all of these studies the concurrent oxytocin infusion period and study populations were different.…”
Section: Introductionmentioning
confidence: 99%